Development of linguistic intelligence based on the triadic conception of the brain - Joya Viancha, Damaris; Afanador Salgado, Dineira; Blanco García, Amalia Yaneth; Florez Ortiz, Xiomara (Rastros Rostros, 2002)
The pedagogical research "Development of linguistic intelligence based on the triadic conception of the brain" was carried out for several years and its population and sample was the educational community of the "Concentración Escolar el Poblado de Girón", grade 5-B of the morning session. This research took as its theoretical basis the authors Waldemar de Gregori with the "Triadic conception of the brain" and Howard Gardner with "The theory of multiple intelligences".